From Expenditure Consolidation to Expenditure Efficiency : Addressing Public Expenditure Pressures in Lithuania - Coady, David (IMF Working Papers; Working Paper, 2015)
This paper reviews public expenditure in Lithuania to identify areas where deeper structural reforms may be warranted to improve spending efficiency and contain future spending pressures. The analysis benchmarks spending in Lithuania against other European countries focusing on spending levels, spending composition, and spending outcomes, and for both economic and functional spending classifications. While recent expenditure consolidation efforts have kept public spending among the lowest in Europe, a transition from broad-based measures to more structural measures will be required: to ensure that low spending levels remain sustainable, to address poor social outcomes such as high inequality and poor health and education outcomes, and to efficiently and equitably contain spending pressures arising from an ageing population.